Prognostic Factors of Malignant Pheochromocytoma and Paraganglioma: A Combined SEER and TCGA Databases Review - Mei, Lin; Khurana, Arushi; Al-Juhaishi, Taha; Faber, Anthony; Celi, Francesco; Smith, Steven; Boikos, Sosipatros (Hormone and Metabolic Research, 2019)
Pheochromocytoma (PCC) and paraganglioma (PGL) are rare malignancies while pathogenesis is strongly influenced by genetics. The prognostic factors of these patients remain poorly defined. We aim to study the epidemiology and survival pattern by analyzing the combination of SEER and Cancer Genome Atlas (TCGA) database. Primary outcome was overall survival (OS) and disease specific survival (DSS). Between 1973 and 2013, a total of 1014 patients with PGL or PCC were analyzed. Younger age and female were associated with better outcomes. The incidence of second primary malignancy in PGL/PCC patients was about 14.6%. This population had a significant longer DSS. Other factors, including surgical resection and origin from of aortic/carotid bodies, conferred remarkable survival advantage. In contrast, distant spread portended worse prognosis. Laterality, race, positive serum catecholamine marker did not demonstrate a significant association with OS and DSS. By analyzing TCGA database with total 184 patients were identified. Eighty out of 184 patients (43.5%) had at least one pathogenic mutation. Female had higher ratio of pathogenic mutations than male (58.7% vs. 41.3%) and NF1 mutation was associated with elderly population. SHDB mutation had higher percentage in male. Twenty-nine patients (15.8%) had 2 or more primary. ATRX was the most common oncogenic mutations in metastatic cohort. In conclusion, younger age, female sex, origin from aortic/carotid bodies, complete surgical resection, regional disease, as well as concomitant second primary malignancies were associated with better prognosis. The prognostic value of radiotherapy and oncogenomics warrants further investigation.
Keywords: pheochromocytoma; paraganglioma; SEER database; TCGA database; prognostic factor